Graphene Potentiates the Myocardial Repair Efficacy of Mesenchymal Stem Cells by Stimulating the Expression of Angiogenic Growth Factors and Gap Junction Protein. (19th March 2015) - Park, Jooyeon; Kim, Yong Sook; Ryu, Seungmi; Kang, Wan Seok; Park, Subeom; Han, Jin; Jeong, Hae Chang; Hong, Byung Hee; Ahn, Youngkeun; Kim, Byung‐Soo
<x xml:space="preserve">Abstract</x> Stem cell therapy has emerged as a potential modality for myocardial infarction treatment. Mesenchymal stem cells (MSCs) exert reparative actions in the injured myocardium mainly through the secretion of paracrine factors. In addition, the overexpression of connexin 43 (Cx43), a gap junction protein, promotes cardiac repair and function restoration. It is known that MSCs in a spheroid form, which have enhanced cell–cell interaction, exhibit enhanced expression of paracrine factors and Cx43. However, cell‐extracellular matrix (ECM) interactions, which also contribute to growth factor expression, are very limited in MSC spheroids. Reduced graphene oxide (RGO) shows high affinity toward ECM proteins, such as fibronectin (FN), and high electrical conductivity. In this study, by incorporating FN‐adsorbed RGO flakes into MSC spheroids, it is possible to enhance the cell–ECM interactions and, subsequently, the paracrine factor expression in the MSCs in spheroids. Cx43 is also upregulated likely due to the enhanced paracrine factor expression and electrical conductivity of RGO. The injection of MSC–RGO hybrid spheroids into the infarcted hearts enhances cardiac repair compared with the injection of RGO flakes or MSC spheroids. This study demonstrates that RGO can effectively improve the therapeutic efficacy of MSCs for ischemic heart diseases.